Prevalence of Anti Hepatitis C Virus (HCV) Antibodies in Cataract Surgery Patients - Maimoona Iqbal, Tahir Mahmood (Pakistan Journal of Ophthalmology, 2008)
Purpose: To find out the prevalence of anti HCV antibodies in patients undergoing cataract surgery. Material and Method: All patients who were advised and scheduled for cataract surgery and were unknown for any liver disease were included in this study. Each subject was serologically screened for anti HCV antibodies and only included in the study with the evidence of positive or negative report. Results: Out of 468 patients who reported for cataract surgery 52 (11.1%) turned out to be positive for HCV virus antibodies. In less than 60 years of age females were more whereas in above 60 years of age males and female were equally positive for anti HCV antibodies. Prevalence of diabetes mellitus in HCV positive patients was 19.2%. Conclusion: The percentage of patients who turned out positive for anti HCV antibodies, who were previously unknown for any liver disease, was significantly higher as compared to the prevalence of carrier state for HCV in general population.